The Effect of Ambient Temperature and Air Humidity on The Body's Hematocrit Levels when Exercising - Nurdin, Reza Febrianto; Bafirman, Bafirman; Susanto, Nugroho; Indika, Pudia M; Agustian, Dede Rahman; Suharmedi, Suharmedi; Zarya, Fiky (Poltekita : Jurnal Ilmu Kesehatan, 2024)
Sport has a crucial role in improving quality of life and health, but the environment including temperature and humidity can affect athletes' performance and health. This study focused on the impact of environmental temperature and humidity on hematocrit levels during exercise in Padang City. Using an ex-post facto design, the study involved 15 football players with pre-test and post-test hematocrit before and after a 10km jog. The results of the study are the body's hematocrit levels when exercising, evidenced by statistical analysis, namely: a). P value < 0.05, 0.034<0.05, b) Hematocrit increase that occurs with a difference of 1.25%, c) t calculate > t table which is 2.331 > 1.753 with α < 0.05.  The normality test shows normally distributed data, validating the results of the analysis. Increased hematocrit is related to oxygen demand and dehydration, which can be exacerbated by high temperatures and humidity. The research underscores the importance of a holistic understanding of the sports environment and the implementation of preventive measures, such as adequate fluid intake. Elevated hematocrit levels can be an indicator of dehydration risk, which can affect physical performance and heart health. Therefore, education on the body's adaptation to environmental changes and safe sports practices needs to be introduced to maintain the health and quality of life of people in environments with high temperatures and humidity. It can be concluded that there is a significant difference in the body's hematocrit levels when exercising with a P value of < 0.05.